A rapid technique for detection of toxigenic and nontoxigenic strains of Aspergillus flavus from maize grains - ASHRAF All KHAN and PANKAJ SHARMA, SANGITKUMAR, MEENA SHEKHAR* (Indian Phytopathology, 2007)
Twenty-five isolates of Aspergillus flavus isolated from maize grains were tested by cultural method for aflatoxin detection, which is inexpensive and rapid. Four isolates were found highly toxigenic with dark red colour development while 8 were moderately toxigenic and 10 mildly toxigenic, which showed dark pink and light pink colour after treatment, respectively. Among all isolates tested, only three isolates viz. AF14 AF20 and AF25 were found non-toxigenic by ammonia vapour test. Among the media tested, maximum colour change was observed for colonies grown on Yeast Ex1ract Sucrose Agar followed by Potato Dextrose Agar and Czapek Dox Agar. All media tested, favoured the aflatoxin production. The results of Ammonia Vapour Test were in agreement up to 92% with the result of toxin detection by thin layer chromatography. The nontoxic strains of A. flavus are being further evaluated for their efficacy as potential biocontrol agent to reduce mould infection in maize grains.